2020
DOI: 10.23947/2334-8496-2020-8-3-61-72
|View full text |Cite
|
Sign up to set email alerts
|

Improve Teaching Capacity at Private Universities in Ho Chi Minh City, Vietnam According to AUN-QA

Abstract: The purpose of this study was to develop an approach to assessing the potential of teachers for the possibility of introducing quality standards of the educational process according to AUN-QA in the higher education system of Vietnam. A survey of teachers and managers of 6 private universities in Ho Chi Minh City was carried out, aimed at assessing the quality of university teachers and their potential to AUN-QA standards. The number of respondents was 172 teachers and 42 managers of the studied universities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…An extant review of research on AUN-QA in higher education shows that 12 studies were published in the Scopus database. The objectives of these studies are varied and have covered different aspects of the network: to study the extent to which universities were ready for AUN-QA assessment (Lam et al, 2020) or to survey students on the AUN-QA checklist followed by a curriculum review towards a competency-based curriculum to replace a knowledge-based one (Limpuangthip et al, 2021); to develop a system architecture of business intelligence to an AUN-QA framework with the purpose of facilitating the assessment (Jantakoon & Wannapiroon, 2017) or an efficient curriculum management ICT-based system to support AUN-QA (Ho et al, 2021); to report a project done at a university to comply with the AUN-QA criteria (Mukhaiyar et al, 2019); and to compare AUN-QA and ABET accreditation (Danielson et al, 2016). Among these 12 studies, three studies were reported on the impacts of the AUN-QA assessments.…”
Section: How Aun-qa Has Impacted Higher Education In Aseanmentioning
confidence: 99%
“…An extant review of research on AUN-QA in higher education shows that 12 studies were published in the Scopus database. The objectives of these studies are varied and have covered different aspects of the network: to study the extent to which universities were ready for AUN-QA assessment (Lam et al, 2020) or to survey students on the AUN-QA checklist followed by a curriculum review towards a competency-based curriculum to replace a knowledge-based one (Limpuangthip et al, 2021); to develop a system architecture of business intelligence to an AUN-QA framework with the purpose of facilitating the assessment (Jantakoon & Wannapiroon, 2017) or an efficient curriculum management ICT-based system to support AUN-QA (Ho et al, 2021); to report a project done at a university to comply with the AUN-QA criteria (Mukhaiyar et al, 2019); and to compare AUN-QA and ABET accreditation (Danielson et al, 2016). Among these 12 studies, three studies were reported on the impacts of the AUN-QA assessments.…”
Section: How Aun-qa Has Impacted Higher Education In Aseanmentioning
confidence: 99%